Changes to postdiagnostic dementia support in England and Wales during the COVID-19 pandemic: a qualitative study. Issue 2 (2nd February 2022) - Wheatley, Alison; Poole, Marie; Robinson, Louise
Abstract : Objectives: To explore the impact of COVID-19 on postdiagnostic dementia care and support provision in England and Wales. Design: Qualitative research using semistructured interviews, via video or telephone conferencing. Setting: Services providing postdiagnostic support across health, social care and the third sector. Participants: 21 professionals previously recruited to an ongoing research programme on postdiagnostic dementia care (or colleagues, if unavailable). Results: Key themes identified from the data were: challenges caused by COVID-19; responses to those challenges, including a widespread shift to remote working; and effects of COVID-19 on future postdiagnostic support. Challenges included changing and sometimes conflicting guidelines; a lack of access to support; identifying and responding to emerging needs; emotional and physical impact of COVID-19; and balancing COVID-19 risk with other risks such as deterioration. Some dementia services closed, while others adapted and continued to provide support thus potentially widening existing inequalities. There were also some unintended positive outcomes, including improved cross-sector and multidisciplinary working between professionals. Conclusion: Delivering postdiagnostic dementia support during COVID-19 required essential adaptations. While some changes were detrimental to service users, others were identified as potentially beneficial and highly likely to become the new 'norm', for example, use of blended approaches, combining virtual and face-to-face work, thus allowing more flexible, integrated care. Our data have implications for policy and practice to improve the response to the lingering effects of COVID-19 as well as creating service provision that is more resilient to future pandemics or other periods of disruption.